PmPPAF is a pro-phenoloxidase activating factor involved in innate immunity response of the shrimp Penaeus monodon - Ma, T.H.T.; Benzie, John A.H.; Jian-Guo He; Cheng-Bo Sun; Siuming F. Chan (Elsevier, 2014)
One of the major steps in the innate immune response of shrimp includes the activation of serine proteinases of the pro-phenoloxidase pathway by the prophenoloxidase activation enzyme (PPAF). In this study, the cDNA encoding a serine proteinase homologue (SPH) with prophenoloxidase activating activity of Penaeus monodon (PmPPAF) was cloned and characterized. PmPPAF cDNA consists of 1444 nucleotides encoding a protein with 394 amino acid residues. The estimated molecular weight of PmPPAF is 43.5 kDa with an isoelectric point of 5.19. PmPPAF consists of a signal peptide, a CLIP domain and a carboxyl-terminal trypsin-like serine protease domain. It is highly similar to the masquerade-like protein 2A (61% similarity) of the crayfish Pacifastacus leniusculus, other serine proteases (42.9–67% identity) of P. monodon, and the PPAF of the crab (61% similarity). Unlike other SPH of P. monodon, which express mainly in the hemocytes, PmPPAF transcripts were detected in the hemocytes, eyestalk, hypodermis, gill, swimming leg and brain. Similar to the crab PPAF, PmPPAF transcript level is high in shrimp at the premolt stages and PmPPAF expression is up-regulated in shrimp infected with white spot syndrome virus (WSSV). Gene silencing of PmPPAF decreased expression of a prophenoloxidase-like gene and injection of Anti-PmPPAF antibody causes a decrease in PO activity. Taken together, these results provided evidence that PmPPAF is a serine proteinase homologue, and is involved in the pro-PO activation pathway of the shrimp innate immune system.